The impact of hearing loss on cognitive impairment: The mediating role of depressive symptoms and the moderating role of social relationships - Cao, Xia; Liu, Qian; Liu, Jiali; Yang, Bingfang; Zhou, Jiansong (Frontiers in Public Health, 2023)
Background: In light of the potential detrimental effects of hearing loss on mental health and cognitive function, it is important to develop an understanding of the mediating and moderating mechanisms of the association between hearing loss and cognitive impairment. The purpose of this study was to determine whether social relationships, including their components, moderate the effects of depressive symptoms as a mediator on MCI. Methods: This study included a total of 8,094 Chinese older adults from the 2018 wave of the Chinese Longitudinal Healthy Longevity Survey (CLHLS). Simple mediation analysis and moderated mediation analysis were conducted to examine the roles of depressive symptoms and social relationships in the association between hearing loss and MCI. Results: There is a significant correlation between hearing loss, depression, social relationships, and cognitive function. Depression partially mediated the association between hearing loss and cognitive function [B = -0.114; 95% confidence interval (CI): (-0.158, -0.076)]. Social relationships moderated the effect of hearing loss on cognitive function through both path b (depression-cognitive function) [B = 0.021; 95 % CI: (0.008, 0.034)], and path c’ (hearing loss-cognitive function) [B = 0.597; 95 % CI: (0.463, 0.730)]. Furthermore, social activities and social networks moderated both direct and indirect effects of moderated mediation. However, there appeared to be no moderated effect of social support for both the direct and indirect paths. Conclusions: Social relationships moderated both the direct and indirect effects of depressive symptoms on the association between hearing loss and cognitive impairment. These findings highlight the mechanisms underlying the relationship between hearing loss and cognitive impairment in Chinese older adults. It might be worthwhile to recommend multidimensional health and social interventions aimed at improving mental health and social inclusion among the olde adults with hearing loss.